Implementation of Patient Safety in Accredited Hospitals and Its Determining Factors in Jambi City, Indonesia - Basok Buharia; Rizanda Machmud; Dorisnita Dorisnita (Elevate, 2018)
Background: Patient safety is an essential part of nursing services and becomes an indicator of the quality of hospital services. Purpose: The general aim of this research was to explore and analyze patient safety and related factors in its application in accredited hospitals. Method: This research was quantitative research. This research used descriptive analytic with cross-sectional approach. Samples were 226 nurses chosen by using proportional random sampling in two accredited hospitals. The sampling used simple random sampling technique. The application of patient safety by the nurses was surveyed by using an instrument that was developed from the regulation of the Minister of health. Meanwhile, the determining factors of the application of patient safety were measured by using Safety Attitudes Questionnaire (SAQ) which consisted of 6 factors; teamwork, safety climate, job satisfaction, perceptions of management, stress recognition, and working condition. Data were analyzed by using chi-square test. Result: The results confirmed that the implementation of patient safety by nurses in the accredited hospitals, more than half were less than good (59%). The result of determining factors analysis was: there was a significant relationship between teamwork, safety culture, stress, management, and working condition and the implementation of patient safety (P = 0,000-0,017), while job satisfaction (P = 0,928) was an irrelevant factor with the application of patient safety. Conclusion: There was a significant relationship between teamwork, safety culture, stress recognition, perception management, and working condition and the implementation of patient safety. This research recommends the necessity to improve policies concerning the evaluation effort of the application of patient safety in the hospitals. Likewise, to evaluate all nursing Standard Operating Procedures (SOP) in terms of patient safety considerations as well as factors that affect them, especially the working condition.